(untitled) (Scottish Archaeological Internet Reports, 2009)
The site was as described by the RCAHMS, with one building taking up the whole of the summit. This building had three compartments, and an access track wound steeply up the west face of the stack leading straight to the entrance of the main compartment. This is one of the few possible medieval castle in the isle of Lewis.